Kemiskinan dan Faktor-Faktor yang Mempengaruhinya di Indonesia - Rukmuin Wilda Payapo; Erly Leiwakabessy; Muhammad Ridhwan Assel (Universitas Batanghari Jambi, 2023)
Poverty alleviation in Indonesia is strongly influenced by other economic variables. The three main factors used to measure its effect on poverty are economic growth, unemployment and inflation. This study aims to examine and analyze the relationship between theoretical and empirical balance between economic growth, unemployment rate and inflation rate with poverty in Indonesia both in the short and long term. The estimation method used is a dynamic econometric model with the cointegration approach and the Error Correction Model (ECM). The results of this study indicate that the equation model used has cointegration relationships and long-term balance between variables. The estimation results show that there is a short-term effect of economic growth, the unemployment rate and inflation on poverty, while in the long term economic growth and the unemployment rate have a significant effect, while inflation is not significant.